BANDSAW BLADE STRESS ОF PORTABLE SAWMILLS (Innovation in Woodworking Industry and Engineering design, 2026)
Studies have been done for the different stresses acting on the bandsaw blade of portable saw mills. The methods for their determination and their impact on the quality of processedsurfaces are analyzed. The relationship between technical parameters of the basic machineunits and bandsaw blade are investigated, as well as their impact on the magnitude of stress.The general guidelines for further research in this area are formulated.